HUMANISTIC APPROACH IN ACTION:EFL WRITING CLASS - Soviyah Soviyah (TEFLIN Journal: A publication on the teaching and learning of English, 2007)
After finishing secondary education level, one can hardly expect that he will be able to perform well in English. One cause is that it is assumed that English learning process emphasizes more on the students cognitive rather than on their psychical needs as human beings. Teachers tend to ignore whatÃ¢â¬â¢s the so called education from the neck up. Based on the writerÃ¢â¬â¢s personal experience during her schooling phase, this paper, therefore tries to offer English teachers the humanistic approach applied in an EFL writing class. This approach is worth considering since its main principle is bringing the learning process towards a more affective situation by combining the subject matter to be learned with the feelings, emotions, experiences, and lives of the students. In this paper, the discussion of what humanistic approach is and why it is worth considering especially in a writing class are elaborated in details. In addition, a model of a classroom application will also be given.